2022
DOI: 10.31616/asj.2020.0608
|View full text |Cite
|
Sign up to set email alerts
|

Use of Parathyroid Hormone and Rehabilitation Reduces Subsequent Vertebral Body Fractures after Balloon Kyphoplasty

Abstract: To evaluate the efficacy of our current prophylactic strategy by investigating the incidence of subsequent vertebral body fractures (SVBFs) following balloon kyphoplasty (BKP). Overview of Literature: Although extensive studies have investigated the risk factors for SVBFs after BKP, few have reported on postoperative therapies to prevent SVBFs and have evaluated their effectiveness. Methods: This study enrolled 273 patients who underwent an initial BKP. To treat osteoporosis, parathyroid hormone (PTH) administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Bisphosphonate and Denosumab therapy were not associated with fracture. In a 2021 retrospective study, among a sample of 273 patients, PTH use was found to be associated with lower rates of remote, but not adjacent, fracture [ 17 ]. Although this study’s results did not show any significant change in vertebral fracture with Denosumab, a RANKL inhibitor, the sample only included five patients on Denosumab therapy, none of whom experienced an adjacent or remote fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonate and Denosumab therapy were not associated with fracture. In a 2021 retrospective study, among a sample of 273 patients, PTH use was found to be associated with lower rates of remote, but not adjacent, fracture [ 17 ]. Although this study’s results did not show any significant change in vertebral fracture with Denosumab, a RANKL inhibitor, the sample only included five patients on Denosumab therapy, none of whom experienced an adjacent or remote fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Ebata et al reported that teriparatide promoted bone formation at the fusion site and decreased bone resorption during the early postoperative period, as indicated by bone turnover markers [26]. Moreover, teriparatide can significantly reduce the risk of additional fractures after a spinal fracture [27]. Since the association between romosozumab and BMP-2 has not been reported, further studies are needed to evaluate the relationship between anabolic agents and BMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Other retrospective studies report the following: teriparatide after BKP is associated with fewer VCFs, increased spine BMD, better health-related quality of life scores, and less back pain versus patients receiving calcium and vitamin D [ 138 ]; teriparatide after BKP is associated with fewer VCFs versus control subjects who mostly received ALN [ 139 ]; and teriparatide after VP is associated with greater vertebral body height and reduced refracture rate versus VP without teriparatide [ 140 ].…”
Section: Effects Of Osteoanabolics On Fracture Healing Arthroplasty S...mentioning
confidence: 99%